Difference of Heat Shock Protein 70 Serum Level Between Primary Angle Closure Glaucoma and Open Angle Glaucoma Patients: Indonesia Single Center Experience - Zuhri, Mohamad Nurdin; Nurwasis, Nurwasis; Retnowati, Endang; Purnomo, Windhu (Folia Medica Indonesiana, 2021)
This study aimed to analyze the differences in Hsp 70 serum levels in patients with primary angle-closure compared to patients with open-angle glaucoma at Dr. Soetomo General Academic Hospital, Surabaya, East Java. This cross-sectional study was conducted on 41 subjects divided into 2 groups consisting of 21 patients with primary angle-closure glaucoma and 20 patients with open-angle glaucoma. Anterior segment examination was assessed by slit-lamp biomicroscope examination. Intraocular pressure on both eyes was measured by Perkin's tonometry. Posterior segment examination was performed with 78 D lens and anterior chamber angle was assessed by goniolens. The serum level of Hsp 70 was assessed using a human Hsp 70 sandwich ELISA kit. The data were statistically analyzed with the Mann-Whitney test. The mean serum levels of Hsp 70 in the primary angle-closure group was 5.55 ï‚± 4.75 ng/ml, while the open-angle group was 3.62 ï‚± 2.39 ng/ml (p = 0.134). There was no difference in Hsp 70 serum levels between the two groups, although the trend obtained serum levels of Hsp 70 patients with primary angle-closure was higher compared to patients with open-angle.